Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Ips Kelas V Sdn Mapala Kota Makassar - Nurhaedah A; Muhammad Amran (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
This research aimed to determine the Application of Cooperative Learning type Snowball Throwing in Improving Learning Outcomes At Subjects IPS In Class V Elementary School Mappala of Makassar, the approach used in this study is a qualitative descriptive type of research is the Classroom action research  cyclical  which  includes planning, implementation, observation, and refleksi. The study population were students of class V Elementary School Mappala Rappocini Subdistrict, City of Makassar numbered 20 people. Data collection techniques of this research is to test, interviews, observations and field notes. Analysis data using descriptive statistical techniques to describe the results of student learning. The results of the study are as follows; (1) by using an approach Cooperative mode Snowball Trawing in Class V Elementary School Mappala can improve student learning outcomes in social studies, (2) the student is already active in the learning approach Cooperative type Snowball Trawing, (3) the teacher is able to carry out learning approach Cooperative tipe Snowball Trawing. an increase in student learning outcomes using a cooperative approach Trawing Snowball type because students on student learning is more active in the implementation of the learning process.